Práticas de ensino e produção de textos escritos na 8ª série do Ensino Fundamental: o quadro europeu comum de referência como ferramenta - SILVEIRA, Jordana Tavares (2009)
In this master's degree dissertation, we developed a study about production of written text in series of 8th series of the elementary school, seeking: to identify the procedures and the observed teacher's habitual difficulties to teach production of written text to their students; Analyzing the didactic material used in those classes; and recommend, just like suggestion, practical of native language teaching to improve the interaction development through written production. As work tool for the development of that study, the Common European Framework of Reference was used (CEFR). Concerning the methodologic procedures, we used the study of case, detaining us to an only group. In the analysis, we thought about the teaching practice of text production, observing thirteen (13) classes of native language and the material in them worked as well as the " compositions " written by the students of the observed class. The results of the research indicate that can change our practice of a teaching of LM descontextualized and without practical and social purpose for the classes that provide the development of the competence students of written production.